Application of image analysis to assessing critical pore size for permeability prediction of cement paste - Hu, Jing (Image analysis and stereology, 2003)
This paper explores image analysis techniques that provide insight into the nature of pore structure as observed in backscattered electron images of polished sections. On the basis of mathematical morphology, the pore size distribution is characterised and the critical pore size is determined for cement paste at different hydration time. The influence of image resolution isinvestigated. The permeability of cement paste can be predicted according toGeneral Effective Media (GEM) theory. Comparison between permeability estimation and experiment results reveals good agreement.
Keywords: Delec, velikost; Materials Testing; Porosity; Materiali, testiranje; Poroznost; Particle Size; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; cementna pasta; mikrostruktura